Construction supply chain - A systematic review - Phu Loc, Tran; Quang Phu, Tran; Thi Yen Thao, Huynh (Journal of Transportation Science and Technology, 2025)
A comprehensive review of the Construction Supply Chain (CSC) has been undertaken to establish a robust theoretical foundation and to identify emerging trends, key challenges, and strategic solutions for advancing the CSC toward sustainability and optimization. A systematic review of 398 scholarly articles published between 2010 and 2025 was carried out using major databases including Emerald, IEEE Xplore, and ScienceDirect. The analysis highlights prominent research directions such as green construction supply chains, risk management, carbon emission control, digital technology integration, modular construction, prefabricated buildings, procurement and collaboration practices, and performance improvement. Technologies such as Building Information Modeling (BIM), Internet of Things (IoT), Blockchain, and Artificial Intelligence (AI) are playing an increasingly critical role in enhancing transparency, real-time monitoring, and risk forecasting. The CSC has been recognized as a strategic development pathway in the context of globalization, contributing to emission reduction, resource optimization, and sustainable development. However, the study also reveals major challenges including fragmentation, risks, and limited capabilities of supply chain participants. Stabilization, strategies such as circular economy integration, resilience enhancement, and performance-based policy design are recommended. The findings serve as a significant scientific and practical basis for the development of the construction supply chain in Vietnam.
Keywords: Construction Supply Chain; Construction Supply Chain management; Construction industry; BIM; Blockchain; Blockchain